Hypoglycaemic unawareness: A systematic review of qualitative studies of significant others' (SO) supportive interventions for patients with diabetes mellitus. Issue 10 (October 2018) - Hartill, E.; Gillis, R.B.; Imran Jiwani, S.; Recchia, N.; Meal, A.; Adams, G.G.
Abstract: Background: Hypoglycemia unawareness (HU) has been attributed to both a downward shift in central nervous system (CNS)-triggered sympatho-adrenal responses to low glycaemic thresholds and a subsequent loss of adrenergic symptoms, which, in addition, to cerebral cortex adaptations permit normal function under hypoglycaemic conditions. Both of these mechanisms are brought about by recurring hypoglycemic events (hypoglycemia-associate autonomic failure, HAAF). This can contribute to repetitive cycles of increasingly severe hypoglycaemia, the consequences of which have considerable impact on relatives and significant others (SO) when providing care to patients with diabetes. Methods: A Systematic Review (SR) of 639 qualitative studies was carried out in accordance with the Preferred Reporting Items for Systematic Review (PRISMA) principles. The search strategy was developed using MeSH terms for a range of electronic databases: CINAHL, Pubmed, EMBASE, Medline, AMED and ASSIA were systematically searched in order to identify a variety of literature relevant to the review topic. Four duplicate studies were removed and a further 630 studies were excluded due to being irrelevant. Five qualitative studies were retained and analysed. Results: The three resultant findings from the literature appraised were i) Experiences and views of Significant Others' (SO) with adult relatives that have HU ii) Support needs of SO and iii) Health professionals interventions to address SO support needs and improve overall HU care. A clear finding was that SO experience difficulties managing HU and this can impact on the relationships that SO and HU patients have. Support needs of SO highlighted were both educational and psychological in nature, with there being a requirement for additional raised awareness within the wider community. Conclusion: It is essential that healthcare professionals offer support, such as teaching and support groups. In addition, providing interventions into improving family knowledge of diabetes and support with regard to psychosocial, behavioural and practical support for the person with diabetes. Moreover, improving resources for families to improve diabetes care. However, as the literature was of a qualitative nature, future recommendations would be quantitative research into these suggested nursing implementations to quantitatively assess their usefulness in practice.